Antitumor Necrosis Factor Agents to Treat Endoscopic Postoperative Recurrence of Crohn's Disease: A Nationwide Study With Propensity-Matched Score Analysis. Issue 8 (3rd August 2020) - Cañete, Fiorella; Mañosa, Míriam; Pérez-Martínez, Isabel; Barreiro-de Acosta, Manuel; González-Sueyro, Ramiro C.; Nos, Pilar; Iglesias-Flores, Eva; Gutiérrez, Ana; Bujanda, Luis; Gordillo, Jordi; Ríos León, Raquel; Casanova, María José; et al.
Abstract : INTRODUCTION: Patients with Crohn's disease experiencing endoscopic postoperative recurrence (POR) may benefit from antitumor necrosis factor (TNF) agents but scarce data on this are available. Our aim was to assess the efficacy of anti-TNF in improving mucosal lesions in patients with endoscopic POR. METHODS: Multicenter, retrospective, study of patients with Crohn's disease who underwent therapy with anti-TNF agents for endoscopic POR (Rutgeerts score > i1). Treatment outcomes were assessed by the findings in the last ileocolonoscopy performed after anti-TNF therapy was initiated. Endoscopic improvement and remission were defined as any reduction in the baseline Rutgeerts score and by a Rutgeerts score < i2, respectively. RESULTS: A total of 179 patients were included, 83 were treated with infliximab and 96 with adalimumab. Median time on anti-TNF therapy at the last endoscopic assessment was 31 months (interquartile range, 13–54). Endoscopic improvement was observed in 61%, including 42% who achieved endoscopic remission. Concomitant use of thiopurines and treatment with infliximab were associated with endoscopic improvement (odds ratio [OR] 2.15, 95% confidence interval [CI] 1.04–4.46; P = 0.03, and OR 2.34, 95% CI 1.18–4.62; P < 0.01, respectively) and endoscopic remission (OR 3.16, 95% CI 1.65–6.05; P < 0.01, and OR 2.01, 95% CI 1.05–3.88; P = 0.04, respectively) in the multivariable logistic regression analysis. These results were confirmed in a propensity-matched score analysis. DISCUSSION: In patients with endoscopic POR, anti-TNF agents improve mucosal lesions in almost two-thirds of the patients. In this setting, concomitant use of thiopurines and use of infliximab seem to be more effective in improving mucosal lesions.